Roles of Plasmacytoid Dendritic Cells in Gastric Cancer - Yang, Jinpu; Liu, Xia; Cheng, Yiwen; Zhang, Jingchen; Ji, Feng; Ling, Zongxin (Frontiers in Oncology, 2022)
Gastric cancer (GC) is the fifth most common neoplasm and the third most deadly cancer in humans worldwide. Helicobacter pylori infection is the most important causative factor of gastric carcinogenesis, and activates innate and adaptive immune responses in the host. As key constituents of the tumor immune microenvironment, plasmacytoid dendritic cells (pDCs) are increasingly attracting attention owing to their potential roles in immunosuppression. We recently reported that pDCs have vital roles in the development of immunosuppression in GC. Clarifying the contribution of pDCs to the development and progression of GC may lead to improvements in cancer therapy. In this review, we summarize current knowledge regarding immune modulation in GC, especially the roles of pDCs in GC carcinogenesis and treatment strategies.